Numerical Development of Concentric Cylinder‐Shaped Dual‐Functional Catalyst Structure for Enhanced Charge Transport in Polymer Electrolyte Fuel Cells. Issue 11 (11th September 2020) - Shin, Seungho; Liu, Jiawen; Chung, Sung‐Jae; Um, Sukkee
Abstract: Dual‐functional catalyst bilayers of vertical concentric cylinders are proposed and numerically developed using a stochastic modeling approach to improve catalyst utilization for advanced fuel cell applications. A cylindrically bilayered catalyst structure wherein the ion transport materials are confined by concentric outer carbon shells is adopted to increase the number of interconnected electron and ion transport paths. For reliable statistical analysis, each data point is extracted from a set of 25 catalyst layer models to achieve a 95% confidence level. The nanoscale morphologies of the ionomers, including interconnected ion transport networks, surface coverage, and electrochemically active surface areas, are quantitatively evaluated. The statistical investigations reveal that the bilayered cylindrical catalyst structures provide more uniform and improved transport paths for ions and reactants when compared with established catalyst layers. Specifically, the additional ion transport channels in the core of the concentric vertical cylinder enhance catalyst utilization under insufficient ionomer conditions. Furthermore, the bilayered catalyst structures yield remarkably enlarged electrochemically active surface areas, hence facilitating more efficient electron, ion, and reactant transfers to improve catalyst utilization. Abstract : A concentric cylinder‐shaped dual‐functional catalyst structure is numerically developed. Statistical investigation confirms that the proposed dual‐functional bilayer catalyst layers provide significantly enlarged electrochemically active surface areas and favorable reactant mass transports to the Pt catalysts. Consequently the bilayered catalyst structures yield significantly improved Pt catalyst utilization by enhancing the formation of species transport networks, especially for ions and reactants.